A Mixed Methods Study to Examine the Influence of CLIL on Physical Education Lessons: Analysis of Social Interactions and Physical Activity Levels - Salvador-García, Celina; Capella-Peris, Carlos; Chiva-Bartoll, Oscar; Ruiz-Montero, Pedro Jesús (Frontiers in Psychology, 2020)
Physical Education is often selected for applying multilingual initiatives through the use of a content and language integrated learning (CLIL) approach. However, it is still unclear whether the introduction of such an approach might entail losing the essence of physical education and distorting its basic purposes. The aim of this study is to analyze the impact of CLIL on physical education lessons. Given the purpose of this study, a mixed methodological approach based on a sequential exploratory design divided into two different phases is used. We begin with initial qualitative data collection (phase I), consisting of the analysis of interviews with 12 participants (8 teachers and 4 students). Based on its analysis, two foci are identified: social relationships and physical activity. Then, informed by the results obtained, a quantitative approach is used (phase II), differentiating these two sets of data to make a more in-depth analysis of them. On the one hand, a sociometric questionnaire was applied to analyze the social relationships between CLIL students. On the other hand, a quasi-experimental design (n = 49) was implemented using accelerometry to measure moderate to vigorous physical activity (MVPA) in the physical education sessions. Regarding physical activity, the results show that levels of MVPA are higher in the experimental group (CLIL) than in the control group, a result which clarifies the divergent viewpoints of the interviewees. However, focusing on social relationships, the sociometric questionnaire results show that there were no statistically significative changes, although some signs of a slight effect on students’ relationships arise depending on their gender. Therefore, more research would be necessary to further study the effect of CLIL in this regard.